Optical pulse compression by photonic devices - Costanzo Caso, Pablo Alejandro (2009)
By combining phase modulation and dispersive transmission on a given time-varying input signal, we propose an optical device for producing ultrashort light pulses of high optical power. We derive the relationship between the required properties of the input signal and the device parameters in order to optimize the energy concentration in the output optical pulses. The high-order aberrations effects of the time lens which perform the phase modulation are considered. Besides, the differences on the obtained pulse shape when the input signal has a gaussian or a super-gaussian envelope are illustrated. Finally, some numerical simulations are shown which illustrate the feasibility of the method.